Analysis of Factors Related to the Incidence of Fluoride Albus in Adolescent Girls at State Junior High School 1 Tilago, Gorontalo Regency - Wanda Djaba; Sirajuddien Bialangi; Nikmatisni Arsad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The World Health Organization (WHO) reports that about 33% of the burden of diseases experienced by women in the world is related to reproductive health problems. In Indonesia, around 90% of women are at risk of developing fluoride albus. Fluorine albus or vaginal discharge is one of the reproductive health problems often experienced by adolescent girls. This study aims to analyze factors related to the incidence of fluoride albus in adolescent girls. This study uses a quantitative design with a cross sectional approach. The population amounted to 83 young women with a sample of 69 respondents selected using purposive sampling techniques. Data analysis using the Chi-Square test as well as the alternative test Fisher's Exact Test. The results showed that there was a significant relationship between attitudes towards reproductive health (p = 0.008), personal hygiene of reproductive organs (p = 0.000), and parental support (p = 0.000) with the incidence of fluorine albus (p < 0.05). There was a significant relationship between attitudes, personal hygiene of reproductive organs and parental support with the incidence of fluoride albus in adolescent girls. It is hoped that schools, health workers, and parents can increase education and coaching related to reproductive health to prevent the occurrence of pathological fluorine albus.